2004
DOI: 10.1111/j.1744-7348.2004.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of tree marigold, Tithonia diversifolia, on cowpea seed bruchid, Callosobruchus maculatus (Coleoptera: Bruchidae)

Abstract: SummaryThe powder and ethanol extract of Tithonia diversifolia leaves were tested for their efficacy at five different concentrations (0.0%, 0.5%, 1.0%, 1.5% and 2.0%) on bruchid mortality, oviposition and adult emergence of cowpea seed beetle Callosobruchus maculatus at ambient tropical storage conditions of temperature and relative humidity. Results showed that the leaf extract had a higher bioactivity on oviposition, adult emergence and mortality of C. maculatus. The mean number of eggs laid on seeds treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 12 publications
5
33
0
Order By: Relevance
“…Javid and Poswal 49 reported that admixing 2% (w/w) powdered flower buds of Syzigium aromaticum with cowpeas prevented oviposition and emergence of Callosobruchus maculatus. This is also in agreement with the findings of Adedire and Akinneye, 50 and Adesina et al 23 who found E. aromatica and A. melegueta significantly reduce or prevent the oviposition and adult emergence of C. maculatus on cowpea. The ability of the evaluated plants to significantly (P<0.05) suppress adult emergence suggested that the plants might possess ovicidal and larvicidal properties.…”
Section: Discussionsupporting
confidence: 82%
“…Javid and Poswal 49 reported that admixing 2% (w/w) powdered flower buds of Syzigium aromaticum with cowpeas prevented oviposition and emergence of Callosobruchus maculatus. This is also in agreement with the findings of Adedire and Akinneye, 50 and Adesina et al 23 who found E. aromatica and A. melegueta significantly reduce or prevent the oviposition and adult emergence of C. maculatus on cowpea. The ability of the evaluated plants to significantly (P<0.05) suppress adult emergence suggested that the plants might possess ovicidal and larvicidal properties.…”
Section: Discussionsupporting
confidence: 82%
“…The current result agrees with previous researchers (Adedire and Akinneye, 2004;Mbailo et al, 2006), who showed that powder and ethanolic extracts of tree marigold, Tithonia diversifolia, seed oils from Azadiracta indica, Ricinus communis, Thevetia nerifolia, Balanites eagyptiaca, Moringa oleifera and Khaya senegalensis protected the stored cowpea seeds against Callosobruchus maculatus infestation.…”
Section: Contact Toxicity and Fumigant Actionsupporting
confidence: 83%
“…The ingredients of these weeds may have the ability to inject into the body of the beetles and dysfunction their nutritional balance, thus caused mortality. Adedire and Akinneye (2004) reported the mortality effect of Tithonia diversifolia flower extracts on C. maculatus. Botanical insecticides offer broad spectrum toxic substances that interrupt insect's normal physiology and behavior, and influence on their feeding, mating, oviposition and mortality (Fouad et al, 2014).…”
Section: Resultsmentioning
confidence: 99%